2016
DOI: 10.3390/ani6090051
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Betaine Impacts the Physiological Responses to Moderate Heat Conditions in a Dose Dependent Manner in Sheep

Abstract: Simple SummaryHeat stress in sheep initiates physiological methods to dissipate heat that result in decreased production. This study investigated the use of a dietary supplement, the osmolyte betaine fed at two doses (2 or 4 g/day), on the physiological responses to heat in sheep. Heat exposure initiated physiological responses such as an increased rectal temperature and respiration rate as expected, while betaine supplemented at 2 g/day ameliorated these responses. Thus, dietary betaine supplementation may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 47 publications
(72 reference statements)
11
51
1
Order By: Relevance
“…Consistent with these results, Hall et al [25] stated that supplementation of betaine at 35 and 70 g/d improved milk production in thermoneutral conditions but not in heat stress. Curvilinear dose responses to betaine supplementation have also been noticed in beef cattle and sheep during HS with improvements at 2 and 15 g betaine per day, respectively [10] [6]. The reason for the moderation in response to high doses of Bet during HS may be that the stimulation of hepatic metabolism and a resultant upsurge in…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with these results, Hall et al [25] stated that supplementation of betaine at 35 and 70 g/d improved milk production in thermoneutral conditions but not in heat stress. Curvilinear dose responses to betaine supplementation have also been noticed in beef cattle and sheep during HS with improvements at 2 and 15 g betaine per day, respectively [10] [6]. The reason for the moderation in response to high doses of Bet during HS may be that the stimulation of hepatic metabolism and a resultant upsurge in…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bet is an amino acid and has the ability to improve the production performance of different animals [1], such as steers [10] and pigs [11]. These results suggest that betaine has the potential to reduce heat stress by reducing energy expenditure [6], thereby reducing metabolic heat production and maintaining osmotic balance in animals facing heat stress.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, DiGiacomo et al (2014) refer to dietary interventions to reduce heat-induced toughening, with particular emphasis on the potential of betaine (trimethylglycine). Although most studies on betaine as a nutritional supplement have been carried out on pigs and poultry for the purpose of reducing heat stress and improving growth performance, reports for beef have shown that betaine was effective in lowering the incidence of high rigor temperature carcasses (Loxton et al 2007), reducing rectal temperatures under both thermo-neutral and heat-challenging conditions in sheep (DiGiacomo 2011), and reducing heart and respiration rates in sheep (DiGiacomo et al 2012). In addition, Wang et al (2010a) showed that betaine was effective in reducing insulin resistance by decreasing non-esterified fatty acids (NEFA) in dairy cattle; further support for this effect in mice and humans was reported by Wang et al (2010b) and Borgschulte et al (2008).…”
Section: Pre-slaughter Interventionsmentioning
confidence: 99%
“…12 As a zwitterion, betaine holds intracellular water molecules against a concentration gradient; 13 therefore, it exerts an osmoprotective effect on cells 14,15 and has been suggested to be an active substance given to animals exposed to osmotic stress-related disorders. 16 Betaine also acts as a thermoprotectant for bacterial cells, 17 and it serves as a methyl donor 18 and a direct substrate for ruminal microbes. 19,20 It can also stabilize native protein structure and prevent molecular disintegration.…”
Section: Introductionmentioning
confidence: 99%